Shiftwork and department-type related to job stress, work attitudes and behavioral intentions : a study of nurses - Jamal, Muhammad [Verfasser]; Baba, Vishwanath V. [Verfasser] (My University, 1992)
"The present study examined the relationship of shiftwork and dpartment-type with employees' job stress, stressors, work attitudes and behavioral intention. Data were collected by means of a strucred questionnaire from nurses (N=1148) working in eight hospitals in a large, metropolitain city in eastern Canada. Results generally support the prediction that nurses working on fixed shifts were off than nurses working on rotating shifts in terms of the dependent variables of the present study. The prediction that nurses working in non-intensive care departments were better off than nurses working in intensive care departments received mixed support at best." (author's abstract) ((en)) Der Beitrag stützt sich auf eine empirische Studie zur Arbeitsbelastung und Arbeitszufriedenheit von Krankenschwestern. Insbesondere wurde der Einfluss von Schichtarbeit und Krankenhausabteilung auf Stress und Arbeitseinstellungen untersucht. (IAB)
Schichtarbeit und Abteilungstyp in Beziehung zur Arbeitsbelastung, Einstellung zur Arbeit und Verhaltensabsichten - Eine Studie über Krankenschwestern
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 2.3 Wandel von Arbeit & Wirtschaft; G 2.4 Sozialer Wandel; G 1.2.2.2 Soziale Sicherungssysteme; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.4.2 Lebenskonzepte, -stile, Werte; P 1.3 Frauen; Krankenschwester; Schichtarbeit; Stress; Berufsrolle; Arbeitskonflikt; Soziale Unterstützung; Arbeitszufriedenheit; Arbeitszeit; Berufswahl; Zufriedenheit; Berufsproblem; Frauen in Einzelberufen; Frauenarbeit; Quantitative Angaben